Challenges Faced by Students in Answering Biology Essay Questions in the English Language - Jelani, M.; Abd Aziz, A.; Hassan, H. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
Effective writing abilities are essential for science students to articulate their thoughts and critical thinking, enabling the assessment of their scientific knowledge progression. This study aims to uncover the challenges Malaysian Higher School Certificate (STPM) students face in answering Biology essay questions in English. Using a document analysis approach, examiners’ feedback from 27 STPM Biology Candidate Reports of essay questions spanning 2013 to 2021 were inductively analyzed. Thematic analysis unveiled the challenges faced by students in answering Biology essay questions in English. The analysis reveals two primary hurdles faced by STPM Biology students. The most substantial challenge pertains to the ‘content’, followed by ‘content and language’. Deficiencies in scientific comprehension and principles were evident within the ‘content’ category. In ‘content and language’, students needed help to compose English responses. Factors like ‘technical term’, content, language, and technical term’, ‘language’, and ‘technical term and language’ held little significance. Intriguingly, ‘content and technical term’ posed the least difficulty; inaccuracies in specialized vocabulary usage caused confusion and point deductions. These findings highlight the substantive challenges STPM Biology students face in the domain of natural science education. The study underscores that prevalent issues addressing STPM Biology essay questions revolve around insufficient content coverage and limited English proficiency. Addressing these challenges and devising instructional strategies to bolster content comprehension and language skills within the natural science context proves pivotal. By tackling these issues, educators and policymakers can cultivate a more supportive and effective learning environment for STPM Biology students.